Catalytic upgrading and enhancing the combustion characteristic of pyrolysis oil - Huynh Van Nam; Dang Nguyen Thoai; Truong Thanh Tam; Van Tho (My University, 2021)
Catalytic upgrading and enhancing the combustion characteristic of pyrolysis oil
Keywords: Dầu nhiệt phân